2006
DOI: 10.1002/hep.21322
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression of glutamine synthetase in rats is controlled by STAT5 and TCF transcription factors

Abstract: In mammalian liver, high glutamine synthetase (GS) expression is restricted to hepatocytes surrounding the terminal venules. The most important enhancer of the GS gene is located Ϸ2520 base pairs (bp) upstream from the transcriptional start point. The nature of the transcription factors that bind to the enhancers has remained enigmatic. In this study, we purified nuclear proteins binding to the element. Supershift assays and footprint experiments with purified protein identified activated STAT5 as a transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…2005) in the 5′‐flanking region of the SOCS‐2 gene (data not shown). Furthermore, to our surprise one of the LEF/TCF sites overlaps with a Stat5b binding site, and another Stat5b binding site is in close proximity to a TCF/LEF site, similar to the far‐upstream enhancer region of the GS gene (Werth et al. 2006).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…2005) in the 5′‐flanking region of the SOCS‐2 gene (data not shown). Furthermore, to our surprise one of the LEF/TCF sites overlaps with a Stat5b binding site, and another Stat5b binding site is in close proximity to a TCF/LEF site, similar to the far‐upstream enhancer region of the GS gene (Werth et al. 2006).…”
Section: Discussionmentioning
confidence: 82%
“…(ii) It has been shown that GH affects the expression of glutamine synthetase (Gebhardt & Mecke 1979). Werth et al. (2006) demonstrated that a Stat5 and a LEF/TCF binding site are important for the induction of GS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV‐loxP‐DsRed‐loxP‐eGFP was described previously . A vector containing glutamate synthetase (GS)/GLUL regulatory element (GSRE) upstream of minimal thymidine kinase promoter (TKp) has been described previously . The GSRE/TKp element was subsequently cloned into an Eco RI/ Ava I site upstream of a Cre‐recombinase in a pTrip lentiviral expression clone.…”
Section: Methodsmentioning
confidence: 99%
“…2) based on the repressor function of TCF in the absence of activated β‐catenin and the release of this repression upon activation of β‐catenin. This may result in binding of STAT5 to the far‐upstream enhancer of the GS gene and regulation of expression by growth hormone signaling (Werth et al,2006; Gebhardt et al,2007). A similar mechanism might be involved in the regulation of cytochrome P450 isoforms, because many of these are also affected by growth hormone signaling (Waxman and O'Connor,2006).…”
Section: Tcf‐dependent Signalingmentioning
confidence: 99%